1984
DOI: 10.1037/0096-3445.113.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Representations of perceptions of risks.

Abstract: The perception of risks (e.g., diseases, accidents, and natural hazards) is investigated using a multitask, multimodel approach. We studied the proximities among 18 risks induced by three tasks: judgment of similarity, conditional prediction, and dimensional evaluation. The comparative judgments (similarity and prediction) were reasonably close, but the dimensional evaluation did not correlate highly with either similarity or prediction. Similarity judgments and conditional predictions appear to be represented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0
3

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(79 citation statements)
references
References 16 publications
4
72
0
3
Order By: Relevance
“…As Johnson and Tversky (1984) have shown, a factor model (or, more generally, a spatial model) is not the only possibility forthe representation ofrisk perception. These authors suggest, as an alternative, a tree model that is based on the assumption that risk is perceived in terms of common and unique discrete features for the hazards being compared, and not in terms of comparing various hazards on a number of common dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…As Johnson and Tversky (1984) have shown, a factor model (or, more generally, a spatial model) is not the only possibility forthe representation ofrisk perception. These authors suggest, as an alternative, a tree model that is based on the assumption that risk is perceived in terms of common and unique discrete features for the hazards being compared, and not in terms of comparing various hazards on a number of common dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…A large body ofresearch has also found that people's perceptions of the acceptability of risks are largely influenced by the characteristics of the hazards they face (see Fischhoff, Slovic, Lichtenstein, Read, & Combs, 1978 ;Johnson & Tversky, 1984; June 1993 -American Psychologist Slovic, Fischhoff, & Lichtenstein, 1980;Slovic, Fischhoff, & Lichtenstein, 1986;Starr, 1969) . Drawing on this research, Hance et al (1988) suggested that people do not simply disregard scientific information about risks .…”
Section: Perceptions Of Riskmentioning
confidence: 99%
“…Psychologists have been very active in investigating and cataloging people's attitudes to different types of hazards (see for example, Fischhoff et al;1978;Lichtenstein, 1980, 1985;Johnson and Tversky, 1984). They have postulated, and empirically tested, various cognitive dimensions by which people assess risk.…”
mentioning
confidence: 99%